ATTITUDE OF YOUTH ABOUT HIV / AIDS PREVENTION AT SMA 4 KOTA BATAM - Haivan Kusuma Aji; Agung Hadi Pramono (Universitas Batam, 2020)
Background : According to the World Health Organization (WHO) HIV continues to be a public health problem globally, having claimed more than 35 million lives so far. In Indonesia since the beginning of the HIV-AIDS epidemic, nearly 78 million people have been infected with HIV and around 39 million people have died due to HIV. Adolescence is easily carried over to bad things such as smoking, having sex, drugs, or free sex and low levels of it. reproductive health knowledge including HIV / AIDS. The purpose of this study was to determine adolescent attitudes about HIV / AIDS prevention. Method : This study used a descriptive research design. The length of the study was 6 months with a population of all class X and XI students of SMA N 4 Batam as many as 353 students, the sampling was systematic random sampling with a sample size of 77 respondents. The research instrument used a questionnaire. Result : Research results Adolescents have a positive attitude as many as 50 respondents (64.9%) and 27 respondents (35.1%) have a negative attitude. Conclusion : The conclusion is that more than half of the respondents are positive. Suggestions for the school it is suggested to be able to collaborate with the BKKBN or puskesmas to establish reproductive health services for adolescents in schools, especially on how to prevent HIV / AIDS so that early students have good attitudes and behavior towards HIV / AIDS.